FUNGSI MODAL SOSIAL DAN HUBUNGANNYA TERHADAP PENGEMBANGAN DESA WISATA BERBASIS COMMUNITY BASED TOURISM (CBT): (SUATU PENELITIAN TENTANG FUNGSI MODAL SOSIAL DAN HUBUNGANNYA TERHADAP PENGEMBANGAN DESA WISATA BERBASIS COMMUNITY BASED TOURISM (CBT) DI DESA GIRIMULYO, KECAMATAN JOGOROGO, KABUPATEN NGAWI TAHUN 2022) (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This thesis is entitled The Use of Social Capital and Its Relationship to Community Based Tourism (CBT) Tourism Village Development in Srambang Park, Girimulyo Village, Jogorogo District, Ngawi Regency in 2022. This research uses quantitative descriptive research procedures, namely research that aims to describe quickly characteristics of a person, condition or indication of a particular group or to determine the frequency of the presence of certain ties between an indication and other indications in society.  Methods of collecting information using the observation method, the questionnaire method, and the method of documentation.  The population of this research is Srambang Park tourism managers, village heads, village features, tourism awareness groups (POKDARWIS) and residents in Girimulyo Village, totaling 100 people. The results of this research show that social capital in Girimulyo Village has doubtful criteria, which means that social capital has not fully participated in the development of Srambang Park tourism. On the other hand, Community Based Tourism (CBT)-Based Tourism Village Development has doubtful criteria, which means that community involvement in the development of a tourist village is still not established in totality. This shows that the Social Capital of the Girimulyo Village residents has a weak bond with the Development of the Srambang Park Tourism Village.